2018
DOI: 10.3390/ijms19113465
|View full text |Cite
|
Sign up to set email alerts
|

Biological Potential and Mechanism of Prodigiosin from Serratia marcescens Subsp. lawsoniana in Human Choriocarcinoma and Prostate Cancer Cell Lines

Abstract: Tripyrrole molecules have received renewed attention due to reports of numerous biological activities, including antifungal, antibacterial, antiprotozoal, antimalarial, immunosuppressive, and anticancer activities. In a screen of bacterial strains with known toxicities to termites, a red pigment-producing strain, HDZK-BYSB107, was isolated from Chamaecyparis lawsoniana, which grows in Oregon, USA. Strain HDZK-BYSB107 was identified as Serratia marcescens subsp. lawsoniana. The red pigment was identified as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 64 publications
4
51
0
1
Order By: Relevance
“…In mammals, the 'caspases' are a highly specific class of cysteine proteases 57 that can initiate/suppress programmed cell death via activation/deactivation of several proteins 91,92 . Treatment with prodigiosin alone and its combination with PU-H71 increased the level of caspase 8 and 9 transcription in contrast to PU-H71, which is in agreement with Li and his colleagues in 2018 93 , stating that the proposed anticancer effects of prodigiosin is caspase-dependent. PU-H71 did not increase caspase 9 level opposing to a previous study that reported the activation of caspase 9 upon using PU-H71 94 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In mammals, the 'caspases' are a highly specific class of cysteine proteases 57 that can initiate/suppress programmed cell death via activation/deactivation of several proteins 91,92 . Treatment with prodigiosin alone and its combination with PU-H71 increased the level of caspase 8 and 9 transcription in contrast to PU-H71, which is in agreement with Li and his colleagues in 2018 93 , stating that the proposed anticancer effects of prodigiosin is caspase-dependent. PU-H71 did not increase caspase 9 level opposing to a previous study that reported the activation of caspase 9 upon using PU-H71 94 .…”
Section: Discussionsupporting
confidence: 88%
“…PU-H71 did not increase caspase 9 level opposing to a previous study that reported the activation of caspase 9 upon using PU-H71 94 . Noticeably, prodigiosin displayed multimodal anticancer potency as a result of caspase-dependent and -independent induction of apoptosis, activation of protein kinase pathways, and induction of cell cycle arrest 93 . Consistent with previous findings, we elucidated that prodigiosin induces mitochondrial-dependent apoptosis by the upregulation of BAX and caspase 9 transcription levels.…”
Section: Discussionmentioning
confidence: 99%
“…5D). Recent literature reported that supernatant metabolites of H. salinarum IBRC M10715 and red pigment-producing HDZK-BYSB107 were able to induce apoptosis in prostate cells via upregulation of caspase 3 20,21 . Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the investigation of natural anticancer drugs has received much interest. Prodigiosin was investigated as a potent natural anticancer agent since it showed strong inhibition against a wide range of human cancer cell lines but lower toxicity toward normal cells [41]. The mechanisms of anticancer activity of prodigiosin were reported in previous studies [41][42][43].…”
Section: Evaluation Of Inhibitory Effect Of Prodigiosin Against Cancementioning
confidence: 99%
“…Prodigiosin was investigated as a potent natural anticancer agent since it showed strong inhibition against a wide range of human cancer cell lines but lower toxicity toward normal cells [41]. The mechanisms of anticancer activity of prodigiosin were reported in previous studies [41][42][43]. Prodigiosin induces apoptosis in various human cancer cells [42], and some possible mechanisms were prosed that prodigiosin as mitogen-activated protein kinase regulators, cell cycle inhibitors, DNA cleavage agents, and pH modulators [43].…”
Section: Evaluation Of Inhibitory Effect Of Prodigiosin Against Cancementioning
confidence: 99%